Alcohol‐related problems experienced by university students in New Zealand - Rob McGee; Kypros Kypri (Elsevier, 2004)
Abstract Objective:To examine reported problems associated with alcohol use in a large sample of New Zealand university students. Method:A random sample (n=1,910) of students at the University of Otago Dunedin was invited to complete an Internet‐based survey of their patterns of alcohol use and associated behaviours. Results:The survey achieved a response rate of 82% (n=1,564). Reports of alcohol‐related problems were relatively common and included the physical consequences of bingeing as well as interpersonal, anti‐social and academic problems. Conclusions:Problems associated with alcohol consumption are relatively common and represent potential harm to the students' immediate health and academic performance. A study of the effects of alcohol on actual academic performance of students is warranted.